2006
DOI: 10.12930/0271-9517-26.1.13
|View full text |Cite
|
Sign up to set email alerts
|

How Do Their Initial Goals Impact Students' Chances to Graduate? An Exploration of Three Types of Commitment

Abstract: Opinions are mixed regarding whether uncertainty about an academic major is detrimental to students beginning their college careers. Early research on this topic painted a rather bleak picture. For instance, Abel (1966) found that students who were rated as having low academic or career certainty had a significantly higher rate of attrition than students who were rated as having a high degree of academic or vocational certainty. Titley and Titley (1980) reported that students who had low certainty regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Empirical research in academic advising has not focused on this relationship despite scholars' assertions that academic advisors play a role in connecting or binding students to institutions (Drake, 2013;Kuh et al, 2005). The results of our study provide empirical underpinnings for the claims (Bean, 2005;Graunke et al, 2006) that academic advising offers a relationship-building strategy for encouraging college students to develop loyalty to their institutions. Students who receive good academic advising may value the personal investment provided them and consider ways to reciprocate to the institution.…”
Section: Connections Between Academic Advising and Loyaltymentioning
confidence: 63%
See 2 more Smart Citations
“…Empirical research in academic advising has not focused on this relationship despite scholars' assertions that academic advisors play a role in connecting or binding students to institutions (Drake, 2013;Kuh et al, 2005). The results of our study provide empirical underpinnings for the claims (Bean, 2005;Graunke et al, 2006) that academic advising offers a relationship-building strategy for encouraging college students to develop loyalty to their institutions. Students who receive good academic advising may value the personal investment provided them and consider ways to reciprocate to the institution.…”
Section: Connections Between Academic Advising and Loyaltymentioning
confidence: 63%
“…In the academic advising literature, specifical ly the NACADA Journal, terms such as loyalty or commitment in relation to advising practice appear infrequently. In fact, we found one article, by Graunke, Woosley, and Helms (2006), that examined the effects of student commitment to their institution, educational goals, and an academic major to graduation. Graunke et al suggested that institutional and goal commitment positively affects the likelihood of students graduating in six years and recommended that advisors work to enhance the students' bond with their institutions.…”
Section: Predictors Of Student Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…While systematic studies of identity status and persistence have not been reported, some studies allow for tentative inferences to be drawn. On the basis of available evidence, one can conclude that persistence seems to be higher for students in the two identity statuses that involve commitment (identity achievement and foreclosure) than the two statuses that do not (moratorium and diffusion); foreclosures do not withdraw at the same rates as moratorium or diffusion students in these studies (Waterman et al, 1974), and Graunke, Woosley, and Helms (2006) reported that students' commitment to a particular major is negatively associated with the probability of completing the requirements for a baccalaureate degree.…”
Section: The Academic Performance Of Foreclosure Studentsmentioning
confidence: 91%
“…Fiscal accountability (accountability) Glennen, Farren, & Vowell, 1996 Focus groups (*) Barrows & Murray, 1997;Dillon & Fisher, 2000;Smith, 2002;Donnelly, 2004;Ryser & Alden, 2005;Simmons, 2005;Kem & Navan, 2006;Baruch-Runyon, Van Zandt, & Elliott, 2009 Follower behavior (student behavior) Lerstrom, 2008 Freshmen Danis & Wall, 1987, 1988Arbuckle & Gale, 1996;Tinto, 1999;Glennen, Martin, & Walden, 2000;McBeth, Richardson, Cregler, & Meyer, 2000;Paul, Manetas, Grady, & Vivona, 2001;DesJardins & Jie, 2002;Maddi, Khoshaba, Jensen, Carter, Lu, & Harvey, 2002;Smith, 2002;Szafran, 2002;Layton & Lock, 2003;McDonald, 2003;Sams, Brown, Hussey, & Leonard, 2003;Yarbrough & Brown, 2003;Gordon, 2004;Abelman & Molina, 2006;Graunke, Woosley, & Helms, 2006;Smith, Dai, & Szelest, 2006;Schwebel, Walburn, Jacobsen, Jerrolds, & Klyce, 2008;Baruch-Runyon, Van Zandt, & Elliott, 2009;Bitz, 2010;Oliver, Ricard, Witt, Alvarado, & Hill, 2010 course/seminar (freshman seminar) Danis & Wall, 1987, 1988…”
Section: Diffusion Of Innovationmentioning
confidence: 99%